Molecular-level effects on cell membrane models to explain the phototoxicity of gold shell-isolated nanoparticles to cancer cells - Camacho, Sabrina Aléssio; Kobal, Mirella Boaro [UNESP]; Almeida Junior, Alexandre Mendes; Toledo, Karina Alves de [UNESP]; Oliveira Junior, Osvaldo Novais de; Aoki, Pedro Henrique Benites [UNESP] (Elsevier, 2020)
Metallic nanoparticles are promising agents for photothermal cancer therapy (PTT) owing to their photostability and efficient light-to-heat conversion, but their possible aggregation remains an issue. In this paper, we report on the photoinduced heating of gold shell-isolated nanoparticles (AuSHINs) in in vitro experiments to kill human oropharyngeal (HEp-2) and breast (BT-474 and MCF-7) carcinoma cells, with cell viability reducing below 50 % with 2.2 × 1012 AuSHINs/mL and 6 h of incubation. This toxicity to cancer cells is significantly higher than in previous works with gold nanoparticles. Considering the AuSHINs dimensions we hypothesize that cell uptake is not straightforward, and the mechanism of action involves accumulation on phospholipid membranes as the PTT target for photoinduced heating and subsequent generation of reactive oxygen species (ROS). Using Langmuir monolayers as simplified membrane models, we confirmed that AuSHINs have a larger effect on 1,2-dioleoyl-sn-glycero-3-phospho-l-serine (DOPS), believed to represent cancer cell membranes, than on 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) taken as representative of healthy eukaryotic cells. In particular, data from polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS) revealed an increased conformational order of DOPS tails due to the stronger adsorption of AuSHINs. Furthermore, light irradiation reduced the stability of AuSHINs containing DOPC and DOPS monolayers owing to oxidative reactions triggered by ROS upon photoinduced heating. Compared to DOPC, DOPS lost nearly twice as much material to the subphase, which is consistent with a higher rate of ROS formation in the vicinity of the DOPS monolayer.

Nanopartículas metálicas são agentes promissores para terapia fototérmica (TFT) em cânceres devido à sua fotoestabilidade e conversão eficiente de luz em calor, mas sua possível agregação continua sendo um problema. Neste artigo, relatamos o aquecimento fotoinduzido de nanopartículas de ouro recobertas com sílica (AuSHINs) em experimentos in vitro com células humanas de carcinoma de orofaringe (HEp-2) e de mama (BT-474 e MCF-7), com redução da viabilidade celular abaixo de 50% com 2,2 × 1012 AuSHINs / mL e 6 h de incubação. Esta toxicidade para as células cancerosas é significativamente maior do que em trabalhos anteriores com nanopartículas de ouro. Considerando as dimensões das AuSHINs, hipotetizamos que a absorção celular não é simples, e o mecanismo de ação envolve o acúmulo nas membranas fosfolipídicas, sendo o alvo da TFT para aquecimento fotoinduzido e geração subsequente de espécies reativas de oxigênio (ROS). Usando monocamadas de Langmuir como modelos de membrana simplificados, confirmamos que AuSHINs têm um efeito maior em 1,2-dioleoil-snglicero-3-fosfo-L-serina (DOPS), que se acredita representar as membranas de células cancerosas, do que em 1,2-dioleoil-sn -glicero-3-fosfocolina (DOPC) considerada como representante de células eucarióticas saudáveis. Em particular, dados de espectroscopia de absorção de reflexão de infravermelho modulada por polarização (PM-IRRAS) revelaram um aumento da ordem conformacional das caudas de DOPS devido à adsorção mais forte de AuSHINs. Além disso, a irradiação reduziu a estabilidade de AuSHINs contendo monocamadas de DOPC e DOPS devido às reações oxidativas desencadeadas por ROS mediante aquecimento fotoinduzido. Em comparação com o DOPC, o DOPS perdeu quase o dobro de material para a subfase, o que é consistente com uma taxa mais alta de formação de ROS na vizinhança da monocamada DOPS.
Keywords: Photothermal cancer therapy; Gold shell-isolated nanoparticles; Langmuir monolayers